Community Perspectives on Social Cash Transfer for Children with Disabilities in Rural Zambia - Viela, Emma; Muzata, Kenneth Kapalu; Simalalo, Magdalene; Ramalia, Aminah (Jurnal Karya Abdi Masyarakat, 2025)
This study explores the perceived benefits and challenges of the Social Cash Transfer (SCT) programme for learners with disabilities in Kalumbila District, Zambia. Using a qualitative case study approach, data were collected through in-depth interviews and focus group discussions involving learners, parents, teachers, and social service officers. The findings reveal that while SCT contributes to improved school attendance and basic educational support, significant barriers persist—including limited awareness, cultural stigma, inadequate outreach, and inconsistent disbursement. Schools played a crucial intermediary role, yet gaps in stakeholder coordination and inclusive communication practices hinder full access for eligible children. The study highlights systemic shortcomings in programme design, especially in addressing the complex needs of children with disabilities. It emphasizes the importance of embedding SCT within a broader inclusive social protection framework, supported by assistive services and multi-level collaboration. Despite offering critical insights, the study is limited by its geographic focus and qualitative scope, which constrain generalizability.